The automatic rubber seed clone identification are presented using reflectance sensor, LDR and PIC - Azman, Siti Harishah (2012)
The automatic rubber seed clone identification are presented using Reflectance sensor, LDR and PIC as a controller. The objective of this project is to create an intelligent and automatic identification of rubber seed using application of Microcontroller PIC 16F877A. The functions of this project are to recognize of the selected best rubber three series by using the reflectance at the surface of rubber seed. This project needs to identify of five type rubber seed clone. There are RRIM 2020, RRIM 2002, RRIM 2024, RRIM 2015, and RRIM 2023. The LDR function as a detection of light because the reflectance sensors need the enough light to operate proper it to recognize the surface of rubber. The reflectance sensor (QTR-1A) is used to recognize the surface of rubber skin and take the sample of reading. In this project, three of reflectance are use to cover up the surface of rubber skin because the sensor is too small and cannot cover all surface of rubber skin. These sensors are also used to measure the percentage of light reflectance from the seed surface. There are two distances of measure to determine whether the distance of a sensor having a same result or not and which one is more accurate. There are 6 mm and 1 mm from sensor to rubber seed. The Microsoft Office Excel is used to analyse the average ADC value and the voltage that cover from sensors.